INTEGRITY, CLEAN, AND TRUSTWORTHY : PEMBENTUKAN DAN PENEGAKAN HUKUM DI ERA DISRUPSI - Prathama, Anak Agung Gede Agung Indra (Universitas Mahendradatta, 2025)
Each state government institution has the same interest in continuing to echo their respective visions and duties in order to achieve public trust. However, in an era like this, it is necessary to pay attention to legal products, is it based on Pancasila values? The problems raised from this article are: Integrity, Clean, and Trustworthy in redefining human values as the formation and enforcement of law in the era of disruption. This research includes doctrinal research using primary legal data/materials, secondary legal data/materials and tertiary legal data/materials. The technique of collecting data/legal materials is carried out with a card system and uses a legislative approach, a factual approach, and a conceptual analysis approach.mThe results of this study are: the principles of Integrity, Clean, and Trustworthy with the formation and enforcement of laws in the era of disruption are certainly very influential, because to ensure that the law always comes with good moral content for the community, it is necessary to have the availability of a collective basis that is agreed upon as a guideline for organizing laws for social life.